Gender Analysis of Commuters Travel Behavior and its Impact on Environmental Emissions - Dhar, Vidisha; Sarker, Anamika; Vishwanath, Amrutha (Calibrating Urban Livability in the Global South, 2024)
In Mumbai, the expanding economy has intensified the demand for efficient public transportation. However, the prevalent dependence on private vehicles, persistent traffic congestion and severely low air quality continues to be significant challenges for the city. While public transportation is crucial, its usage has declined (Comprehensive Transport Study, MMRDA, 2021) due to various challenges faced by commuters, particularly women. According to a World Bank study (Dappe & Dappe 2023), women comprise 32% of public transit users, whereas their male counterparts account for 24%. Despite the notable preference exhibited by women for public transit modes, the absence of gender-disaggregated data presents a challenge in accurately capturing their experiences and needs. It is essential to capture the subjective experiences of women commuters to foster a deeper understanding of women's perspectives and facilitate the development of inclusive solutions in the realm of public transportation. This study bridges the gap of unavailable gender disaggregated data by collating insights on travel choices from 515 commuters, with a specific focus on women, utilizing participatory methodologies such as surveys and semi-structured interviews. These surveys and interviews are specifically designed to capture the subjectivities which shed light on the disparity between men and women travel behaviour and the special needs of women commuters. Based on the mode choice of the participants, the study assesses environmental emissions generated based on gender and income categories. The study collates the challenges faced by women in accessing public transit and reveals that women exhibit a greater reliance on walking and public transit, culminating in lower per capita carbon emissions compared to their male counterparts in Mumbai.